2012
DOI: 10.1071/sb12010
|View full text |Cite
|
Sign up to set email alerts
|

Flower biology and subspecies concepts in Micropholis guyanensis (Sapotaceae): evidence of ephemeral flowers in the family

Abstract: Micropholis guyanensis (A.DC.) Pierre is a tree from the rainforests of tropical South America and includes two recognised and one informal subspecies. The species has a wide geographic distribution from Central America, northern and western South America to Amazonia and Bolivia, and is morphologically variable. All subspecies occur in the Reserva Florestal Adolpho Ducke just outside Manaus, Amazonas State in Brazil, and it can be questioned how they can grow in sympatry and retain their identity. We have stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…However, classification of Sapotaceae has been notoriously difficult and different systems have been proposed (Baehni, 1938(Baehni, , 1965Lam, 1939;Aubréville, 1964;Pennington, 1990Pennington, , 1991, leading to unnatural and practically inconvenient classifications, mainly due to high degrees of morphological homoplasy Swenson et al, 2008a,b). Furthermore, circumscriptions of genera and species are prone to large uncertainties (Terra-Araujo et al, 2012b;Gomes et al, 2013), while conservation assessments have suggested that many species of Neotropical Sapotaceae are extinct, threatened to extinction, or endangered (IUCN Red List, 2013). Pennington (1990) revised Sapotaceae for the Neotropics, but over the last decade numerous additional species have been described (Pennington, 2006;Alves, 2011, 2012a,b;Morales, 2012;Terra-Araujo, 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…However, classification of Sapotaceae has been notoriously difficult and different systems have been proposed (Baehni, 1938(Baehni, , 1965Lam, 1939;Aubréville, 1964;Pennington, 1990Pennington, , 1991, leading to unnatural and practically inconvenient classifications, mainly due to high degrees of morphological homoplasy Swenson et al, 2008a,b). Furthermore, circumscriptions of genera and species are prone to large uncertainties (Terra-Araujo et al, 2012b;Gomes et al, 2013), while conservation assessments have suggested that many species of Neotropical Sapotaceae are extinct, threatened to extinction, or endangered (IUCN Red List, 2013). Pennington (1990) revised Sapotaceae for the Neotropics, but over the last decade numerous additional species have been described (Pennington, 2006;Alves, 2011, 2012a,b;Morales, 2012;Terra-Araujo, 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomena of supra-annual flowering and vegetative intraspecific morphological variation mean that flower and fruit analysis is necessary for correct identification of many Sapotaceae species. However, obtaining specimens with intact floral structures is not always possible because of the ephemeral nature of flowers from some species ( Terra-Araujo et al , 2012 ). Therefore, additional methods, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of reproductive biology, virtually nothing is known about Sapotaceae except for three species of Planchonella in New Caledonia (Méndez & Munzinger, ) and one species of Micropholis (Griseb.) Pierre in South America (Terra‐Araujo et al ., ). Taken together, these examples point toward a diversity of situations that could have led to the evolution of cryptic species in New Caledonia such as differences in substrate type and disjunctions between areas with the same type of substrate, all of which may have contributed to this process.…”
Section: Discussionmentioning
confidence: 97%